Globalization, communication and the concept of space in global history - Wenzlhuemer, Roland (Historical social research, 2010)
To study changing patterns of communication, interactions and transfers is a principal focus of global history. Such shifting connectivity patterns produce new spaces that co-exist with and are complementary to geographic space. The creation, transformation and interaction of these spaces become a central object of study in global history if we want to understand processes of globalization — such as the alleged "shrinking of the world". At the same time, practitioners of global history constantly struggle with spatially delineating their field of study. Therefore, global history needs a new understanding of space that provides a framework for both — looking at space as an object of study as well as clearly identifying and demarcating the field of study. In this article, I propose an abstract, multi-layered and strictly relativistic understanding of space that will help the global historian to better master both challenges.
Gesehen am 29.11.2023
Keywords: Geschichte 1800-1900; Globalisierung; Telekommunikation